The Effect of Placement and Competence on Employee Performance through Motivation as an InterveningVariable (Bank Case study, Mandiri Gandaria Branch) - Jasmine Putri Dewi; Harry Indratjahyo; Bongsu Saragih (Krisnadwipayana International Journal of Management Studies, 2022)
This study aims to determine the effect of job placement and competence onemployee performance with work motivation as an intervening variable at PT.Bank Mandiri Gandaria Branch. The sample used in this study were 100employees who worked at the Gandaria branch office by using a questionnaire tocollect data. The sampling technique used a saturated sample. Data analysistechnique using path analysis produces validity, reliability, classical assumptiontest using multicollinearity test, path test and hypothesis testing. The resultsshowed that the variable placement and competence have a significant effect onemployee performance variables through indirect motivation, placementvariables affect employee performance through motivation, competencevariables affect employee performance through motivation. The placementvariable has a direct effect on employee performance, the competence variablehas a significant effect on employee performance.